A food science and foodservice interdisciplinary framework for the development of sorghum and wheat products - Cairns, Aidan Caroline (My University, 2025)
Interdisciplinary Course Framework A framework for two undergraduate food product development courses involving interdisciplinary work between food science and foodservice (university dining center) was implemented. Former students were surveyed to determine framework impact. Students agreed that the framework gave them experience with larger-scale food production equipment, and taught about foodservice perspectives (feasibility requirements, how dining centers operate) and the scale-up process. Students also developed research/laboratory skills, soft skills, and food production knowledge. In return, new recipes were developed for the dining center. This framework could be implemented at other universities to develop interdisciplinary relationships between dining centers and food science programs. Development and Scale-Up of Gluten-Free Sorghum-Based Bakery Goods for Kansas State Dining Services To create new product opportunities for sorghum in the state of Kansas, the FarmUs project had three primary pillars: Innovate, Scale, and Connect. The project aims to close the gap between industry and consumers by peaking interest in sorghum, its nutritional and sustainable benefits, and consumption of sorghum-based products. The primary focus of this study was to develop and scale-up three gluten-free sorghum-based products for Kansas State Dining Services. The secondary objective was to evaluate the sensory and physical properties of these products to provide developmental and research experience for students. Preliminary testing involved identifying optimum ratios of sorghum flour, xanthan gum, starch, and eggs for proper binding. Whipped egg whites were tested at different levels for product volume and texture. Repetition and reformulation of the products provided various renditions of each product. Quantity equipment needs; staffing feasibility, ingredient availability, and cost were determined. Dining staff evaluated each product and once recipes were finalized, parameters (color, specific gravity, internal temperature, moisture loss, height/width, water activity) were evaluated. Dining center customers provided acceptability feedback for the three gluten-free products using the 9-point Hedonic scale. The first product, a savory waffle, can be stacked with turkey sausage and cheddar cheese for a breakfast sandwich. It utilizes sorghum flour, egg whites, xanthan gum, starch, and flaxseed for structure. This product received a range of 7.03–7.63 (n = 43) for all sensory attributes (acceptability, flavor, mouthfeel, texture, and aftertaste). The lemon blueberry muffin contains sorghum flour, eggs, buttermilk, xanthan gum, potato starch, and egg whites. Sensory data (n = 49) measured at acceptability (7.4), flavor (7.6), mouthfeel (6.4), texture (6.6), and aftertaste (7.6). The third product, a sweet potato muffin top, contains sorghum flour, xanthan gum, eggs, egg whites, and sweet potatoes. All three recipes were formatted via Computrition Menu Management system to provide methodology, nutritional analysis, costing, and labeling for university dining use. These recipes, along with sorghum-based educational materials, were shared with higher learning facilities across Kansas. The Impact of Rum on Physicochemical Properties of Sorghum and Wheat Pound Cakes Sorghum, a sustainable flour for gluten-free baked-products, typically results in products with decreased volume, less flexible crumb, and gritty mouthfeel. Ethanol can affect starch properties by increasing gelatinization, swelling, and surface wrinkling, but these effects have not been tested in a cake system. One previous study evaluated rum in wheat cakes and observed increased elasticity and volume. The objective of this study was to evaluate the impact of rum on sorghum and wheat-based pound cakes. A 2x2 factorial design (n=3) was used to compare pound-cake formulations: sorghum with rum (SR), sorghum without rum (SN), wheat with rum (WR), and wheat without rum (WN). White pearled sorghum flour or soft wheat flour was used with rum (7.58%), xanthan gum (0.25%) and potato starch (4.9%) by weight. Water was used instead of rum in the control formulations (SN and WN). Specific gravity (SG) of the batters was determined immediately after mixing. Cakes were baked in pup-loaf pans and cooled for 1h prior to testing. Finished products were evaluated for weight, volume (using laser topography), internal structure (using the C-Cell imaging system), and texture (hardness and cohesiveness, using a texture analyzer fitted with a 2.5cm probe). Data was analyzed using SAS Proc Mixed and Tukey’s test (p<0.05). Sorghum-based batters had lower SG than their wheat counterparts, indicating higher air entrapment during mixing. Rum significantly decreased the SG for both grains. Final volume for wheat-based cakes was higher than sorghum, indicating better air retention, despite formulation with xanthan gum and potato starch for structure-creation. In contrast with SG data, rum significantly decreased cake volume. It also increased top concavity for SR and WR, indicating structural collapse. Regarding internal structure, rum led to an increased number of air cells in SR, and decreased cell wall thickness for both SR and WR. SR had lower hardness compared with WR, while WR presented increased cohesiveness. No differences for bake loss (5.9-6.6%) were noted. Aeration, collapse, and gluten structures play important roles in cake quality. Sorghum and rum contributed to more batter aeration; however, cakes containing sorghum and/or rum had lower volumes. The increased top concavity suggests delay or inadequate structure setting. With the current trend for alcohol-flavored baked goods, understanding the ingredient functionality of alcohol in baked goods can improve future products. This work indicates product structure is of primary concern in both wheat and gluten-free flours.
Keywords: Food science; Foodservice; Sorghum; Interdisciplinary; Gluten-free; Alcohol